Evaluation of the effectiveness of the biomic LiSi connect spray in the securing bond between zirconia and resine cement - صقر, ريما (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: There is a constant effort to treat the surface of zirconia in many different ways to improve its bond with the resin cement, as it is a crystalline ceramic, as grinding with aluminum oxide granules is still the gold standard. A new material was introduced, which is (Biomic LiSi connect spray) containing a glass ceramic to be applied over the surface of zirconia to improve its bond With resin cement and to reduce cases of debonding in fixed prosthodontics Aim of the study: To evaluate the effectiveness of (Biomic LiSi connect spray) in treating the surface of zirconia to increase its bond with resin cement compared to the traditional method of sandblasting with aluminum oxide granules. Materials and methods: The research sample consisted of 20 zirconia discs, which were turned using CAD/CAM technology. The sample was divided equally into two groups according to the surface treatment of the zirconia: 10 discs were placed in the sandblasting group with aluminum oxide granules, 10 discs were placed in the Biomic LiSi connect sprayer, they were cemented to the buccal surfaces of healthy upper premolars prepared with a specific area and thickness using dual-cured resin cement. They were kept in water for 24 hours at a temperature of 37 degrees, then shear bond strength tests were conducted using a universal test machine, and the results were recorded. Results: The results of the T student test for independent samples at the 95% confidence level showed that there were statistically significant differences in the average values ​​of the amount of resistance to shear forces in megapascals between the two groups in favor of the Biomic LiSi connect spray group. Conclusions: Within the limits of this study, we conclude: Biomic LiSi connect spray contributed to improving and increasing the bond of the zirconia surface with the resin cement more effectively than the traditional method using sandblasting with aluminum oxide granules.